Silent natural words in Al-Farazdaq’s poetry (a semantic statistical study) - Iman Ali Khamees, Lect. Dr. (lark, 2025)
The study included the silent nature words in Al-Farazdaq’s collection of description, meaning, and statistics. This study was divided into an introduction and three sections: The first section included the impact of the environment on Al-Farazdaq’s poetry and the silent expressions of nature The second section included the silent natural words most used in the Diwan of Al-Farazdaq and their lexical meanings that appeared in the Diwan. The third section included linguistic issues in terms of the lexical semantic level with statistical study Then comes the conclusion, which explains the most prominent results reached by the researcher.